Continuous improvement: a comparison between Islamic and conventional approaches - Afrin, Afroza Bulbul; Islam, Rafikul (McGraw Hill Education (India) Pvt Ltd, 2019)
Continuous improvement in products/services is one of the vital elements of Total Quality Management (TQM). TQM is not a one-step activity; rather it is a continuous approach and a never-ending process. In order to strengthen competitive advantage in the market, organisations must endeavour to continuously improve quality of products and services. One may call it Jidoka or Kaizan or PDSA or 5-S or 6 sigma or JIT, the purpose is all the same, which is to improve continually either product/service quality or process quality. All of the mentioned models basically focus on the mundane world benefits only. But the proposed NAIS model for continuous improvement is more comprehensive and it focuses benefits in both the worlds –Here and Hereafter. To develop a model of continuous improvement from an Islamic perspective and to find out the distinction between Islamic approach and conventional approaches to continuous improvement are the major objectives of this present study. By nature, the present study is an exploratory one, at the same time it is a theoretical one based on the library research and only the secondary data collected from different relevant literatures, Qur’an and Sunnah are used to realize the objectives.